2016
DOI: 10.1007/s00464-016-5064-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intestinal perfusion by ICG fluorescence imaging in laparoscopic colorectal surgery with DST anastomosis

Abstract: ICG fluorescence imaging is useful for determining the transection line in laparoscopic colorectal surgery with DST anastomosis. Anticoagulation therapy and preoperative chemotherapy are important risk factors for poor intestinal perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 33 publications
(65 reference statements)
1
67
0
2
Order By: Relevance
“…Blood supply to the anastomosis is also thought to be an important factor for AL, and decreased blood flow is a risk factor 22,23) . Since it has been reported that realtime assessment of blood flow around an anastomosis with indocyanine green is acceptable 24) , further study to objectively evaluate the blood flow is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Blood supply to the anastomosis is also thought to be an important factor for AL, and decreased blood flow is a risk factor 22,23) . Since it has been reported that realtime assessment of blood flow around an anastomosis with indocyanine green is acceptable 24) , further study to objectively evaluate the blood flow is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…by blood flow evaluation in the anastomosis site by ICG fluorescence imaging in colorectal cancer. 9,10 We also reported the effectiveness of predicting AL in colorectal cancer surgery with a quantitative laparoscopic ICG fluorescence imaging for the first time. In that report, T0, the time from the administration of ICG to first observation of fluorescence, might be a useful parameter for prediction AL.…”
Section: Introductionmentioning
confidence: 97%
“…Využívá se běžně v jiných indikacích, např. k hodnocení jaterních funkcí, k angiografii v očním lékařství, ke stanovení prokrvení tkání, hledání spá dových lymfatických uzlin [23,24,28]. Neměla by být použita u pacientů s aler gií na jod.…”
Section: Obr 2 Foto Z Operace -Otevření Dutiny Břišní a Patrná Mléčunclassified